Impact of diabetes mellitus on mortality rates and outcomes in myocardial infarction - Schmitt, Volker H.; Hobohm, Lukas; Münzel, Thomas; Wenzel, Philip; Gori, Tommaso; Keller, Karsten (Diabetes & metabolism, 2021)
Background - Diabetes mellitus (DM) represents a major cardiovascular risk factor for increased risk of coronary artery disease and myocardial infarction (MI). DM is also associated with a poorer clinical outcome in MI. - Materials and methods - The nationwide German inpatient population treated between 2005 and 2016 was used for statistical analyses. Hospitalized MI patients were stratified by the presence of DM and investigated for the impact of DM on in-hospital events. - Results - In total, 3,307,703 hospitalizations for acute MI (37.6% female patients, 56.8% aged ≥ 70 years) treated in Germany during 2005-2016 were included in this analysis. Of these patients, 410,737 (12.4%) died while in hospital. Overall, 1,007,326 (30.5%) MI cases were coded for DM. While the rate of MI patients with DM increased slightly over time, from 29.8% in 2005 to 30.7% in 2016 (β = 7.04, 95% CI: 4.13-9.94; P <  0.001), their in-hospital mortality decreased from 15.2% to 11.5% (β = -0.36, 95% CI: -0.38 to -0.34; P <  0.001). Rates of in-hospital death (13.2% vs 12.1%; P <  0.001) and recurrent MI (0.8% vs 0.6%; P <  0.001) were higher in MI patients with vs without DM. Also, in MI patients with DM, significantly lower use of coronary artery angiography (51.5% vs 56.8%; P <  0.001) and interventional revascularization (37.6% vs 43.9%; P <  0.001) was noted. - Conclusion - Although in-hospital mortality of patients with MI decreased in both diabetes and non-diabetes patients, in-hospital deaths were still higher in diabetes patients, thereby revealing the impact of this metabolic disorder on cardiovascular outcomes.
Online first: 28 November 2020, version of record 20 February 2021
Gesehen am 11.08.2022